WOODBALL SPORT CLUB MANAGEMENT STATE UNIVERSITY OF SEMARANG, CENTRAL JAVA PROVINCE - Priagung,; Raharjo, Bambang Budi; Raharjo, Bambang Budi; Hartono, Mugiyo (International Journal of Psychosocial Rehabilitation, 2020)
Research It aims to describe the management of club sports woodball Semarang State University in terms of (1) Human resources management organization management. (2). Management of the trainer training program. (3) infrastructure management (4) Funding management. This research was conducted in the city of Semarang, Central Java Province. The method used is descriptive qualitative research subjects management of woodball sports clubs Semarang State University. Data sources in the form of documents, results of interviews: (funding sources, human resources, infrastructure, training programs) records related to the organization, the achievements of the Semarang State University woodball club using snowball sampling techniques. Mechanical collection of data including reviewing documents, files (content evaluation), interview depth (depth interviewing), and observation (observation). The results showed that: (1) the management of the woodball Unnes club management carried out the organization's management by following the principles of correct management. 2) Trainers and Athletes have a clear training program, regularity in implementation and on target. 3) the availability of infrastructure has not fully completed the majority has been adequate in quality special athlete, but not in quantity for users outside of the athlete, and delivery mechanism tool has carried out correctly, but the utilization of the infrastructure is rudimentary been unable to meet for the number of students outside the athletes. 4) systematic bookkeeping of funds obtained in the form of championship rewards, Cash BKOM (Student Parents Communication Board) and the University. The funds obtained are used effectively and efficiently as needed, the management can look for alternative solutions to other sources of funding.